Coffea arabica: An Emerging Active Ingredient in Dermato-Cosmetic Applications - Grațiana Ruse; Alex-Robert Jîjie; Elena-Alina Moacă; Dalia Pătrașcu; Florina Ardelean; Alina-Arabela Jojic; Simona Ardelean; Diana-Simona Tchiakpe-Antal (Pharmaceuticals)
Background: Coffea arabica, commonly known as Arabica coffee, has garnered attention in recent years for its potential applications in dermato-cosmetic formulations. This review aims to critically evaluate the emerging role of Coffea arabica as an active ingredient in skin care products, focusing on its bioactive compounds derived from both the leaves and beans, mechanisms of action, and efficacy in dermatological applications. A comparative analysis between the bioactive profiles of the leaves and beans is also presented to elucidate their respective contributions to dermato-cosmetic efficacy. Results: This review synthesizes findings from various studies that highlight the presence of key bioactive compounds in Coffea arabica, including caffeine, chlorogenic acids, and flavonoids. Notably, the leaves exhibit a higher concentration of certain phenolic compounds compared to the beans, suggesting unique properties that may enhance skin health. These compounds have demonstrated significant anticellulite, anti-inflammatory, antioxidant, photoprotective, anti-aging, antibacterial, and moisturizing properties. Discussion: This article delves into the biochemical pathways through which bioactive compounds derived from both the leaves and beans of Coffea arabica exert their beneficial effects on skin and hair health. Furthermore, this review highlights the growing trend of incorporating natural ingredients in cosmetic formulations and the consumer demand for products with scientifically substantiated benefits. Conclusions: The findings of this review underscore the potential of Coffea arabica as a valuable active ingredient in dermato-cosmetic applications. Its multifaceted bioactivity suggests that it can contribute significantly to skin health and cosmetic efficacy. Future research should focus on clinical trials to further validate these benefits and explore optimal formulation strategies for enhanced delivery and stability in cosmetic products.